N-Acetylcysteine Reduces ROS-Mediated Oxidative DNA Damage and PI3K/Akt Pathway Activation Induced by Helicobacter pylori Infection. (26th April 2018) - Xie, Chuan; Yi, Jian; Lu, Jing; Nie, Muwen; Huang, Meifang; Rong, Jianfang; Zhu, Zhenhua; Chen, Jiang; Zhou, Xiaoliang; Li, Bimin; Chen, Haiming; Lu, Nonghua; et al.
Abstract : Background . H. pylori infection induces reactive oxygen species- (ROS-) related DNA damage and activates the PI3K/Akt pathway in gastric epithelial cells. N -Acetylcysteine (NAC) is known as an inhibitor of ROS; the role of NAC in H. pylori -related diseases is unclear. Aim . The aim of this study was to evaluate the role of ROS and the protective role of NAC in the pathogenesis of H. pylori -related diseases. Method . An in vitro coculture system and an in vivo Balb/c mouse model of H. pylori -infected gastric epithelial cells were established. The effects of H. pylori infection on DNA damage and ROS were assessed by the comet assay and fluorescent dichlorofluorescein assay. The level of PI3K/Akt pathway-related proteins was evaluated by Western blotting. The protective role of N -acetylcysteine (NAC) was also evaluated with in vitro and in vivo H. pylori infection models. Results . The results revealed that, in vitro and in vivo, H. pylori infection increased the ROS level and induced DNA damage in gastric epithelial cells. NAC treatment effectively reduced the ROS level and inhibited DNA damage in GES-1 cells and the gastric mucosa of Balb/c mice. H. pylori infection induced ROS-mediated PI3K/Akt pathway activation, and NAC treatment inhibited this effect. However, the gastric mucosa pathological score of the NAC-treated group was not significantly different from that of the untreated group. Furthermore, chronic H. pylori infection decreased APE-1 expression in the gastric mucosa of Balb/c mice. Conclusions . An increased ROS level is a critical mechanism in H. pylori pathogenesis, and NAC may be beneficial for the treatment of H. pylori -related gastric diseases linked to oxidative DNA damage.